Board-Level Ku-Band Power Amplifier: Design and Challenges. Issue 4 (4th July 2022) - Singhal, Hemant Kumar; Rawat, Karun
ABSTRACT: This paper describes the challenges in the design of board-level Ku-band power amplifier (PA) using the hybrid-MIC technology. The selection of laminates, connectors, cables and RF components, such as DC feed and DC block, is examined from the perspective of Ku-band PA designers. Other key challenges, such as die mounting and wire bonding, are also discussed. Die mounting and wire bonding are critical phenomena and they have a great impact on the working of PA at high frequencies. After several trials, successful die mounting has been achieved and a methodology for reliable die mounting and wire bonding has been proposed. With the help of investigation done for the design of PA at the high operating frequency, a first board-level power amplifier at 17 GHz has been designed using a 250 nm bare die device with a 400 MHz frequency band.